1992
DOI: 10.1159/000126230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex and Age on Pyridostigmine Potentiation of Growth Hormone-Releasing Hormone-Induced Growth Hormone Release

Abstract: Previous studies have shown that pyridostigmine (PD) is capable of increasing the growth hormone (GH) response to GH-releasing hormone (GHRH) in young healthy subjects. In order to investigate the influence of age and sex on the PD potentiation of GHRH-induced GH release, we have studied the GH response to GHRH (50 µg i.v.) 1 h after oral administration of placebo or PD (60 mg) in 8 young healthy men (aged 19-28 years) and 8 age-matched young women (aged 18-25 years) during the follicular phase of the menstrua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Differences between the two studies include the higher dose of PHYSO used by Raskind et al [14] , and their not having recorded side effects following its administration. Overall, our results appear to be closest to those of Corsello et al [19] , who found greater PYRI-DO potentiation of GH responses to GHRH in elderly subjects vs. their younger counterparts.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Differences between the two studies include the higher dose of PHYSO used by Raskind et al [14] , and their not having recorded side effects following its administration. Overall, our results appear to be closest to those of Corsello et al [19] , who found greater PYRI-DO potentiation of GH responses to GHRH in elderly subjects vs. their younger counterparts.…”
Section: Discussionsupporting
confidence: 87%
“…As indicated in the Introduction, there are only a few prior cholinergic challenge studies that considered women and men separately, to which we can compare our GH fi ndings [12,13,19] . In these studies, PYRIDO was administered orally and at fi xed doses rather than based on Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations